The Influence of Equitable Instructional Practices and Teachers’ Pedagogical Competence on Student Learning Engagement in Inclusive Schools in Indonesia - Istiarsyah Istiarsyah; Dela Devita; Eka Yuli Astuti; Pelita Hayati; Irda Rafika (Westscience Press, 2026)
This study investigates the effect of equitable teaching practices and teachers' pedagogical competence on student engagement in inclusive schools in Indonesia. A quantitative approach was adopted, with data collected from 225 respondents using a Likert-scale survey. The study examines the relationships between equitable teaching practices, pedagogical competence, and student engagement in inclusive classrooms. Data analysis was conducted using SPSS version 25, including descriptive statistics, correlation analysis, and regression analysis. The findings indicate that both equitable teaching practices and teachers' pedagogical competence significantly predict student engagement, with equitable teaching practices having a stronger influence. The study suggests that inclusive teaching strategies and enhancing teachers’ pedagogical competence are essential for fostering student engagement in inclusive classrooms. These findings provide valuable insights for educators and policymakers working to improve inclusive education practices in Indonesia.